253 Idiopathic intracranial hypertension causing back pain and visual loss without headache. Issue 12 (14th November 2019) - Cheema, Sanjay; Cooper, Sarah
Abstract : Idiopathic intracranial hypertension (IIH) usually presents in overweight young women with headache and visual disturbance. We report a case in a slim young woman, who described six months of increasingly severe lower back pain, worse on lying flat and often waking her at night. Despite a significantly elevated cerebrospinal fluid (CSF) opening pressure of 55cm CSF, at no point did she experience a headache. The back pain entirely resolved as CSF pressure was treated. No secondary cause was found on brain or spinal imaging and CSF constituents were normal. She sustained some early and permanent visual loss and required a shunt procedure to control the raised intracranial pressure and ongoing visual deterioration. She has remained well, 20 months since the original presentation. Our patient had pre-existing ocular hypertension, which did not resolve after effective treatment of the raised intracranial pressure and may have affected the presentation of papilloedema. This case highlights that IIH should be considered in patients with visual symptoms and back pain, even in the absence of headache, and acts as a reminder that patients with IIH are not necessarily overweight.